Base excision repair processing of abasic site/single-strand break lesions within clustered damage sites associated with XRCC1 deficiency. - Mourgues, S; Lomax, M; O'Neill, P (2007)
Ionizing radiation induces clustered DNA damage, which presents a challenge to the cellular repair machinery. The repair efficiency of a single-strand break (SSB) is approximately 4x less than that for repair of an abasic (AP) site when in a bistranded cluster containing 8-oxoG. To explore whether this difference in repair efficiency involves XRCC1 or other BER proteins, synthetic oligonucleotides containing either an AP site or HAP1-induced SSB (HAP1-SSB) 1 or 5 bp 5' or 3' to 8-oxoG on the opposite strand were synthesized and the repair investigated using either nuclear extracts from hamster cells proficient (AA8) or deficient (EM7) in XRCC1 or purified BER proteins. XRCC1 is important for efficient processing of an AP site in clustered damage containing 8-oxoG but does not affect the already low repair efficiency of a SSB. Ligase I partly compensates for the absence of the XRCC1/ligaseIII during short-patch BER of an AP site when in a cluster but only weakly if at all for a HAP1-SSB. The major difference between the repair of an AP site and a HAP1-SSB when in a 8-oxoG containing cluster is the greater efficiency of short-patch BER with the AP site compared with that for a HAP1-SSB.